Die Bedeutung von Fachhochschulen für die regionale Wirtschaftsentwicklung: Eine Darstellung am Beispiel der Fachhochschule Niederrhein - Hamm, Rüdiger; Wenke, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
This article deals with the importance of the “Niederrhein University of Applied Sciences” (NUAS) for regional development in the Middle Lower Rhine Area. After some general theoretical considerations, the demand-side effects of the university are estimated by means of a regional multiplier analysis. The most important supply-side effects are analysed through a survey of firms. This shows that the university is noticed by only two thirds of regional enterprises, and that courses of study, activities in research and development and in further education, and also other potentials for co-operation, are scarcely recognised by the firms. The NUAS thus has a serious image problem.
Keywords: Article